2001
DOI: 10.7863/jum.2001.20.7.739
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of anatomic results after the pubovaginal sling procedure for stress urinary incontinence.

Abstract: Objective. To investigate the anatomic changes after the pubovaginal sling procedure in women with stress urinary incontinence by transrectal sonography. Methods. This study enrolled 56 women with varying types of stress urinary incontinence who were treated with the pubovaginal sling procedure using self-fashioned polypropylene mesh. The suburethral sling was fixed without tension and was placed at the position between the bladder neck and the proximal urethra. The patients were investigated preoperatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The possible pathogenesis of de novo urge symptoms includes bladder outlet obstruction and damage to bladder autonomic innervation by the sling procedure 23 . In addition, bladder neck incompetence on transrectal sonography is reportedly closely related to postoperative urgency or urge incontinence 19 . In this study, bladder neck incompetence on transrectal sonography was significantly higher in the distal urethra group but was not significantly associated with de novo urge symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…The possible pathogenesis of de novo urge symptoms includes bladder outlet obstruction and damage to bladder autonomic innervation by the sling procedure 23 . In addition, bladder neck incompetence on transrectal sonography is reportedly closely related to postoperative urgency or urge incontinence 19 . In this study, bladder neck incompetence on transrectal sonography was significantly higher in the distal urethra group but was not significantly associated with de novo urge symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…Because of the high mortality of this inflammatory disease, early diagnosis is essential to initiate adequate surgical and medical treatment. At the present time, MRI cannot identify synthetic slings, although translabial ultrasonography can identify it [10,11] since the polypropylene slings are highly echogenic and easily identified posterior to the urethra. However, nor MRI or ultrasound can identify synthetic sling in obturator foramen.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 3 SUI, the sling was not fi xed and was placed with mild tension in order to produce more urethral resistance. Previous sonographic investigation using the pubovaginal sling procedure of this study demonstrated a thick endopelvic fascia lying between the sling and the urethra [15] . This endopelvic fascia buffer helps prevent the development of bladder outlet obstruction; however, it might also result in inadequate compression of the urethra by the sling.…”
Section: Discussionmentioning
confidence: 99%